“In the Tiles of its Foliage”: The Grandchild’s perspective and “Branching Out” expressions in the Poetry of Gabriel PreilOut” Preil - Popliker, Yotam (MiKAN, 2024)
This article is dedicated to the Hebrew and Yiddish American poet Gabriel Preil, on his thirtieth yahrzeit. It attends to Preil’s “thin” verse, which expresses the perspective of the grandchild and his poetic relationship with his so-called grandfathers. The article argues that this lyrical and sensitive poetic utterance was shaped in the Hebrew and Yiddish American habitat of the first half of the twentieth century, and takes into consideration the complexity of the literary, social and ideology relations it holds. Exploring Preil’s habitat, the article argues that the grandchild’s perspective and its derivatives offer a new historiographical, theoretical and poetic prism for understanding Preil’s verse. Thus, his “branching out” poetics, in analogy to the tree’s foliage, does not express a modernistic will for discursive control but a modest understanding of cultural neighboring, seeing contemporary poets and poetic trends as companions and partners.